African ancestry is associated with cluster-based childhood asthma subphenotypes - Lili Ding; Dan Li; Michael Wathen; Mekibib Altaye; Tesfaye B. Mersha (BMC, 2018)
Abstract Background Childhood asthma is a syndrome composed of heterogeneous phenotypes; furthermore, intrinsic biologic variation among racial/ethnic populations suggests possible genetic ancestry variation in childhood asthma. The objective of the study is to identify clinically homogeneous asthma subphenotypes in a diverse sample of asthmatic children and to assess subphenotype-specific genetic ancestry in African-American asthmatic children. Methods A total of 1211 asthmatic children including 813 in the Childhood Asthma Management Program and 398 in the Childhood Asthma Research and Education program were studied. Unsupervised cluster analysis on clinical phenotypes was conducted to identify homogeneous subphenotypes. Subphenotype-specific genetic ancestry was estimated for 167 African-American asthmatic children. Genetic ancestry association with subphenotypes/clinical phenotypes were determined. Results Three distinct subphenotypes were identified: a moderate atopic dermatitis (AD) group with negative skin prick test (SPT) and preserved lung function; a high AD group with positive SPT and airway hyperresponsiveness; and a low AD group with positive SPT and lower lung function. African ancestry at asthma genome-wide association study (GWAS) SNPs differed between subphenotypes (64, 89, and 94% for the three subphenotypes, respectively) and was inversely correlated with AD; each additional 10% increase in African ancestry was associated with 1.5 fold higher in IgE and 6.3 higher odds of positive SPT (all p-values < 0.0001). Conclusions By conducting phenotype-based cluster analysis and assessing subphenotype-specific genetic ancestry, we were able to identify homogeneous subphenotypes for childhood asthma that showed significant variation in genetic ancestry of African-American asthmatic children. This finding demonstrates the utility of these complementary approaches to understand and refine childhood asthma subphenotypes and enable more targeted therapy.